Sustainable tourism after COVID-19 insights and recommendations for Asia and the Pacific (Asian Development Bank, 2021)
Examines tourism in Asia and the Pacific, the impacts on it of the coronavirus disease (COVID-19) pandemic, and how it might be reset to contribute more effectively to the Sustainable Development Goals.